2008
DOI: 10.1590/s0100-39842008000500005
|View full text |Cite
|
Sign up to set email alerts
|

O valor da fase sem contraste na tomografia computadorizada do abdome

Abstract: OBJECTIVE: To determine the role of the unenhanced phase of abdominal computed tomography in patients without a definite diagnosis or undergoing tumor staging. MATERIALS AND METHODS: A prospective and transversal study was developed with 100 consecutive patients submitted to unenhanced and contrastenhanced abdominal computed tomography. Two observers evaluated all the computed tomography images in the contrast-enhanced phase (first analysis) and, later, in the unenhanced phase (second analysis) in an attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…Iannaccone et al (8) , in 2005, reported that the combined use of the arterial, portal and equilibrium phases present sensitivity and positive predictive value of 92.8% and 97.3%, respectively, for detection of HCC in cirrhotic patients, concluding that the non-contrast-enhanced phase does not add value to justify its utilization for the investigation of such tumors. In 2008, Leite et al (9) evaluated 100 patients with undefined clinical indication or in tumor staging/re-staging, demonstrating that the non-contrast-enhanced phase is not indispensable for such evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iannaccone et al (8) , in 2005, reported that the combined use of the arterial, portal and equilibrium phases present sensitivity and positive predictive value of 92.8% and 97.3%, respectively, for detection of HCC in cirrhotic patients, concluding that the non-contrast-enhanced phase does not add value to justify its utilization for the investigation of such tumors. In 2008, Leite et al (9) evaluated 100 patients with undefined clinical indication or in tumor staging/re-staging, demonstrating that the non-contrast-enhanced phase is not indispensable for such evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Among such strategies, the suppression of some of the studies' phases seems to be a practical and safe way to achieve dose reduction, since the reliability and diagnostic accuracy of the exams are maintained (9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When such strategies are applied together, a significant reduction is observed in the radiation dose to which the patient is exposed (6) , in some specific clinical situations attaining equivalent doses lower than 2 mSv (23) , which correspond to three views of plain abdominal radiography or one cranial CT (25) . Besides the above mentioned strategies, suppression of one or more imaging phases has been showing to be a feasible and effective alternative (7,11) . In the present study, considering the evaluation of a wide range of clinical indications, frequently with four acquisition phases, the authors obtained an estimated mean effective dose of 41.2 mSv per scan, with an average of 12.5 mSv per phase.…”
Section: Discussionmentioning
confidence: 99%
“…Imbriaco et al analisaram exames com suspeita de câncer de pâncreas e demonstraram que a realização de apenas uma fase pós-contraste era o suficiente para um diagnóstico e estadiamento desta neoplasia (IMBRIACO et al, 2005). Leite et al concluíram que a fase sem contraste não era fundamental para o diagnóstico em várias indicações clínicas (LEITE et al, 2008). Metser et al comprovaram que para detecção de tumores do trato urinário alto e baixo, a fase portal é mais eficiente que a fase de equilíbrio, sendo esta última desnecessária para o seu diagnóstico (METSER et al, 2012).…”
Section: Dose Em Um Exame De Tcunclassified